2016
DOI: 10.1016/j.bone.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of proteasome inhibitors on bone remodeling in multiple myeloma

Abstract: Bone disease is a characteristic feature of multiple myeloma, a malignant plasma cell dyscrasia. In patients with multiple myeloma, the normal process of bone remodeling is dysregulated by aberrant bone marrow plasma cells, resulting in increased bone resorption, prevention of new bone formation, and consequent bone destruction. The ubiquitin–proteasome system, which is hyperactive in patients with multiple myeloma, controls the catabolism of several proteins that regulate bone remodeling. Clinical studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 90 publications
1
34
0
Order By: Relevance
“…Preclinical and clinical data also showed that these inhibitors have a beneficial effect on bone remodeling by stimulating bone formation and suppressing bone resorption (21). In this study, we demonstrated in culture and in an animal model that suppressing the 26S proteasome by proteasome inhibitors accelerates DNA repair in osteoblasts and protects them from radiationinduced apoptosis, thus protecting bones from radiation damage.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Preclinical and clinical data also showed that these inhibitors have a beneficial effect on bone remodeling by stimulating bone formation and suppressing bone resorption (21). In this study, we demonstrated in culture and in an animal model that suppressing the 26S proteasome by proteasome inhibitors accelerates DNA repair in osteoblasts and protects them from radiationinduced apoptosis, thus protecting bones from radiation damage.…”
mentioning
confidence: 50%
“…It has been well documented that Bzb treatment increases bone-forming markers, such as alkaline phosphatase, and suppresses bone resorption markers, such as CTX and TRAP-5b, in patients with multiple myeloma (41). Preclinical studies showed that Bzb primarily stimulates bone formation by promoting osteoblast differentiation using multifaceted mechanisms, such as up-regulation of Runx2 activity, active b-catenin level, osterix, and vitamin D signaling, stabilization of Runx2 protein, and downregulation of DKK1, a Wnt pathway inhibitor (21). Our study uncovered a new mechanism for the anabolic bone action of Bzb, i.e., stimulation of DNA repair to preserve osteoblasts after radiation insult.…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib promoted osteoblast differentiation from mesenchymal stem cells in vitro . Consistent with that observation, proteasome inhibitor treatment has been noted to restore bone homeostasis in human multiple myeloma patients, by stimulating differentiation of bone‐forming osteoblasts, while suppressing the maturation and activity of pro‐resorptive osteoclasts . In contrast, bortezomib has also been reported to impair bone growth in young mice, through chondrocyte toxicity .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, treatment with bortezomib resulted in increases in homogenous contrast agent uptake within the BM in both femur and tibia. Bortezomib causes significant marrow remodeling, resulting in reduction in osteoclast activity and cytokine secretion, and inhibition of tumor‐induced angiogenesis . At the same time, healing and tumor cell death induced by bortezomib may also generate increased inflammation, which may result in an increase in contrast uptake within high tumor burden regions after relapse.…”
Section: Discussionmentioning
confidence: 95%